Multicentre prospective survey of SeHCAT provision and practice in the UK. Issue 1 (1st May 2016) - Summers, Jennifer A; Peacock, Janet; Coker, Bolaji; McMillan, Viktoria; Ofuya, Mercy; Lewis, Cornelius; Keevil, Stephen; Logan, Robert; McLaughlin, John; Reid, Fiona
Abstract : Objective: A clinical diagnosis of bile acid malabsorption (BAM) can be confirmed using SeHCAT (tauroselcholic ( 75 selenium) acid), a radiolabelled synthetic bile acid. However, while BAM can be the cause of chronic diarrhoea, it is often overlooked as a potential diagnosis. Therefore, we investigated the use of SeHCAT for diagnosis of BAM in UK hospitals. Design: A multicentre survey was conducted capturing centre and patient-level information detailing patient care-pathways, clinical history, SeHCAT results, treatment with bile acid sequestrants (BAS), and follow-up in clinics. Eligible data from 38 centres and 1036 patients were entered into a validated management system. Results: SeHCAT protocol varied between centres, with no standardised patient positioning, and differing referral systems. Surveyed patients had a mean age of 50 years and predominantly women (65%). The mean SeHCAT retention score for all patients was 19% (95% CI 17.8% to 20.3%). However, this differed with suspected BAM type: type 1: 9% (95% CI 6.3% to 11.4%), type 2: 21% (95% CI 19.2% to 23.0%) and type 3: 22% (95% CI 19.6% to 24.2%). Centre-defined 'abnormal' and 'borderline' results represented over 50% of the survey population. BAS treatment was prescribed to only 73% of patients with abnormal results. Conclusions: The study identified a lack of consistent cut-off/threshold values, with differing centre criteria for defining an 'abnormal' SeHCAT result. BAS prescription was not related in a simple way to the SeHCAT result, nor to the centre-defined result, highlighting a lack of clear patient care-pathways. There is a clear need for a future diagnostic accuracy study and a better understanding of optimal management pathways.